Design Of Automation Institutional Repository Library System Of Web-Based National University Using Open Source "Senayan 9: Bulian: Design Of Automation Institutional Repository Library System Of Web-Based National University Using Open Source "Senayan 9: Bulian - Muhammad Rayhan; Moh. Iwan Wahyuddin; Winarsih Winarsih (Jurnal Mantik, 2020)
The rapid technological development in the Digital Age spurred every organization to participate in implementing it in order to facilitate work and improve services. The library as a repository of professional institutions also participated in implementing the automation system. The National University as a professional institution also needs to develop an automation system that applies Free Open Source Software (FOSS) technology. The Senayan Library Management System (SLiMS) application that utilizes WEB-based on FOSS can be implemented as a repository automation system. Compared to other library automation systems, SLiMS 9: Bulian has many advantages. In addition, SLiMS has a large community network in almost every city in Indonesia and even abroad.